Preparation of fowl testes as recipient organs to germ-line chimeras by means of gamma-radiation - Trefil, P; Polak, J; Poplstein, M; Mikus, T; Kotrbová, A; Rozinek, J (British poultry science, 2003)
1. The aim of the study was to investigate the possibility of preparing adult fowl testes for the production of exogenous germ-lines by eradication of recipient spermatogenesis using gamma-radiation. 2. A comparison between several radiation therapy treatments (based on 60Co isotope) of male testes was conducted using gamma-rays of 18, 22 and 26 Gy in a single dose or repeated doses of 5 x 8 Gy over a 15-d period. Sperm concentration and motility were determined after each treatment. 3. Altered spermatogenesis was observed after a single treatment dose of 18 Gy, while single doses of 26 Gy were followed by reduced sperm numbers (from 22 x 10(9) to 31 x 10(6) sperm/ml) within 60 to 100 d after treatment. After a single treatment of 26 Gy sperm motility was reduced by 50%. In contrast, a fractionated treatment (5 x 8 Gy) with gamma-rays halted spermatogenesis 39 d after the distribution of the first 8 Gy dose. 4. Observations of the seminiferous tubules by electron microscopy performed 12 months after this treatment confirmed that moderate doses of gamma-rays (8 Gy) distributed repeatedly (5 x) over a limited period (15 d) sterilise adult fowl testes but maintain morphologically normal somatic (Leydig and Sertoli) cell populations.
Keywords: buněčná membrána; spermie; testis; Gamma Rays; Chickens; Sperm Count; Female; fertilizace; záření gama; zvířata; Regression Analysis; časové faktory; Fertilization; kur domácí; Cobalt Radioisotopes; ženské pohlaví; Testis; Male; počet spermií; Chimera; Spermatozoa; Animals; Cell Membrane; radioizotopy kobaltu; mužské pohlaví; chiméra; Time Factors; regresní analýza